Development of Persistent Respiratory Morbidity in Previously Healthy Children After Acute Respiratory Failure*. Issue 8 (August 2020) - Keim, Garrett; Yehya, Nadir; Spear, Debbie; Hall, Mark W.; Loftis, Laura L.; Alten, Jeffrey A.; McArthur, Jennifer; Patwari, Pallavi P.; Freishtat, Robert J.; Willson, Douglas F.; Straumanis, John P.; Thomas, Neal J.
Abstract : Objectives: Acute respiratory failure is a common reason for admission to PICUs. Short- and long-term effects on pulmonary health in previously healthy children after acute respiratory failure requiring mechanical ventilation are unknown. The aim was to determine if clinical course or characteristics of mechanical ventilation predict persistent respiratory morbidity at follow-up. Design: Prospective cohort study with follow-up questionnaires at 6 and 12 months. Setting: Ten U.S. PICUs. Patients: Two-hundred fifty-five children were included in analysis after exclusion for underlying chronic disease or incomplete data. One-hundred fifty-eight and 130 children had follow-up data at 6 and 12 months, respectively. Interventions: None. Measurements and Main Results: Pulmonary dysfunction at discharge a priori defined as one of: mechanical ventilation, supplemental oxygen, bronchodilators or steroids at 28 days or discharge. Persistent respiratory morbidity a priori defined as a respiratory PedsQL, a pediatric quality of life measure, greater than or equal to 5 or asthma diagnosis, bronchodilator or inhaled steroids, or unscheduled clinical evaluation for respiratory symptoms. Multivariate backward stepwise regression using Akaike information criterion minimization determined independent predictors of these outcomes. Pulmonary dysfunction at discharge was present in 34% of patients. Positive bacterial respiratory culture predicted pulmonary dysfunction at discharge (odds ratio, 4.38; 95% CI, 1.66–11.56). At 6- and 12-month follow-up 42% and 44% of responders, respectively, had persistent respiratory morbidity. Pulmonary dysfunction at discharge was associated with persistent respiratory morbidity at 6 months, and persistent respiratory morbidity at 6 months was strongly predictive of 12-month persistent respiratory morbidity (odds ratio, 18.58; 95% CI, 6.68–52.67). Positive bacterial respiratory culture remained predictive of persistent respiratory morbidity in patients at both follow-up points. Conclusions: Persistent respiratory morbidity develops in up to potentially 44% of previously healthy children less than or equal to 24 months old at follow-up after acute respiratory failure requiring mechanical ventilation. This is the first study, to our knowledge, to suggest a prevalence of persistent respiratory morbidity and the association between positive bacterial respiratory culture and pulmonary morbidity in a population of only previously healthy children with acute respiratory failure. Abstract : Supplemental Digital Content is available in the text.